Billington: Victorian executioner - Bruce, Alison (The History Press, 2023)
'An insightful and gripping account that will take you into the dark but fascinating world of a Victorian executioner.' - Stewart P. EvansBetween 1884 and 1905 James Billington and his three sons, Thomas, William and John, were responsible for 235 executions in Victorian Great Britain and Ireland. They hanged many notorious murderers, but equally fascinating is the story of the family. Did James really feel he served society and justice, or did this position satisfy something more personal?Billington: Victorian Executioner provides a complete account of the stories behind James Billington's executions, as well as the real man behind the rope - a man whose business was death. This enthralling biography is an exciting addition to any true crime bookshelf